Soils, water and nutrients in a forest ecosystem in Suriname - Poels, R.L.H.; Agricultural University Wageningen, Wageningen (Países Bajos) (Agricultural University, Wageningen (Países Bajos), 2014)
253 páginas : Incluye ilustraciones y tablas.